The effect of TEVAR for blunt traumatic thoracic aortic injury on maximal aortic diameter: Mid- and long-term outcome. (August 2019) - Mufty, Hozan; Maleux, Geert; Houthoofd, Sabrina; Cornelissen, Sandra A; Daenens, Kim; Bonne, Lawrence; Fourneau, Inge
Objective: Thoracic endovascular aortic repair (TEVAR) has become the standard of care for blunt thoracic aortic injury (BTAI). Long-term effects of TEVAR on the aortic diameter are not well studied. This study evaluates the effect of TEVAR for BTAI on the aortic diameter in mid- and long-term follow-up. Methods: All patients treated with TEVAR for BTAI between August 2000 and May 2016 were included. Maximum aortic diameter was measured at four predetermined thoracic aortic levels in the preoperative and first postoperative CT angiography (CTa) and in the last control CTa or MR angiography: 1 cm proximal (D1) and 1 cm distal to the left subclavian artery (D2), 3 cm distal to the left subclavian artery (D3) and 3 cm proximal to the celiac trunk (D4). Results: A total of 27 patients (20 men, mean age 40 years (±17.55) were included. Mean follow-up time was 90 months (±48.36)). No re-interventions were needed. Mean growth of aortic diameter at level D1, D2, D3 and D4 was 0.22 mm ± 3.66, 1.79 mm ± 3.82, 0.73 mm ± 4.18 and –1.06 mm ± 2.82, respectively, when comparing last follow-up to the preoperative imaging without any statistical significant differences. When comparing the preoperative diameter with the first postoperative CT, only a statistical significant growth of 2.81 mm ± 2.69 was seen at level of D2 ( p  < 0.05) Conclusion: During mid- to long-term follow-up, a temporary significant increase of the maximum aortic diameter was seen at level D2 in the direct postoperative phase This increase was not associated with clinical events and suggests long-term efficacy of TEVAR after BTAI.